Managing salesmen (Middlesex : Rank Aldis Industrial Services, 1900)
This film tackles the vital job of training people to manage a sales force. The importance of a sales manager is becoming increasingly recognised as the results achieved by a sales team are a reflection of the performance of the sales manager.
Keywords: Sales personnel; Sales management